2011
DOI: 10.1002/ijc.25466
|View full text |Cite
|
Sign up to set email alerts
|

CHI3L1 (YKL‐40) is expressed in human gliomas and regulates the invasion, growth and survival of glioma cells

Abstract: Chitinase 3-like 1 (CHI3L1) is a secreted glycoprotein that has pleiotropic activity in aggressive cancers. In our study, we examined the expression and function of CHI3L1 in glioma cells. CHI3L1 was highly expressed in human glioma tissue, whereas its expression in normal brain tissue was very low. CHI3L1 suppression by shRNA reduced glioma cell invasion, anchorage-independent growth and increased cell death triggered by several anticancer drugs, including cisplatin, etoposide and doxorubicin, whereas CHI3L1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 38 publications
7
95
0
Order By: Relevance
“…Notably, among these 12 genes, 5 (ARG2, CHI3L1, FAM134B, KRT17, and CD6) have prosurvival functions and/or are associated with transformation and poorer clinical outcome in human cancers. [43][44][45][46][47][48][49] Next, we confirmed that a subset of these genes is dependent on HIF1-a for hypoxia-induced upregulation. As shown in Figure 7B, knockdown of HIF1-a resulted in abrogation of the hypoxia-induced upregulation of ARG2, BNIP3, SULF2, and NEDD9.…”
supporting
confidence: 55%
“…Notably, among these 12 genes, 5 (ARG2, CHI3L1, FAM134B, KRT17, and CD6) have prosurvival functions and/or are associated with transformation and poorer clinical outcome in human cancers. [43][44][45][46][47][48][49] Next, we confirmed that a subset of these genes is dependent on HIF1-a for hypoxia-induced upregulation. As shown in Figure 7B, knockdown of HIF1-a resulted in abrogation of the hypoxia-induced upregulation of ARG2, BNIP3, SULF2, and NEDD9.…”
supporting
confidence: 55%
“…Many of the mucins, which are frequently mutated or overexpressed in cancers (43), were up-regulated, especially Muc5B, Muc13, and Muc3a. Finally, Chitinase 3-like 1 (CHI3L1), which is also expressed in human gliomas (44) and promotes angiogenesis in colorectal cancer (45), is increased. PKA.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, CHI3L1 (Chitinase 3-like 1), a secreted glycoprotein, which has been implicated in invasion and cell matrix adhesion (62), was observed at higher levels in the secretome of U87 cells (58,59) and was present at lower levels in the EGFR-and EGFRvIII-expressing cell lines compared with U87 parental, ϩPE-and ϩPTEN-expressing cells. For the ϩPE cell line, 32 proteins were detected and CTSL1 protein; an endopeptidase inhibitor was present at the highest level.…”
Section: Pten-and Pe-expressing Cell Lines Had Low Abundance Of Invasmentioning
confidence: 99%
“…CHI3L1 is a secreted glycoprotein highly expressed in gliomas that has been shown to increase invasion (59), and elevated levels of CHI3L1 in serum have been associated with poor prognosis (62,106). All glioma cell lines secreted CHI3L1 protein and surprisingly, both ϩPE and ϩPTEN secreted high levels of the glycoprotein indicating PTEN's influence on secretion of CHI3L1.…”
Section: Proteins Involved In the Epithelial-mesenchymal Transition (mentioning
confidence: 99%